Pengujian Aplikasi Invoice Untuk Freelancer Small Business Berbasis Web Dengan Metode Blackbox - Shintania, Mira; Ananda, Angga Thifal; Perdana, Anggi; Fadlurrohman, Muhammad Shiddiq; Zy, Ahmad Turmudi (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Freelancers and small businesses often require invoices for their business operations, whether it be for collaboration with larger companies or for recording transactions and invoicing clients. Testing is conducted using the Black Box Testing method with the Equivalence Partitions technique. The goal is to determine whether the system functions as intended, ensuring that users do not encounter any issues. The results of this testing reveal no functional errors, and it can be concluded that the system is operating smoothly and ready for use.